2021
DOI: 10.3389/fmed.2021.761601
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Uptake, Acceptance, and Hesitancy Among Persons With Mental Disorders During the Second Stage of China's Nationwide Vaccine Rollout

Abstract: Persons with mental disorders (PwMDs) are a priority group for COVID-19 vaccination, but empirical data on PwMDs' vaccine uptake and attitudes toward COVID-19 vaccines are lacking. This study examined the uptake, acceptance, and hesitancy associated with COVID-19 vaccines among Chinese PwMDs during China's nationwide vaccine rollout. In total, 906 adult PwMDs were consecutively recruited from a large psychiatric hospital in Wuhan, China, and administered a self-report questionnaire, which comprised standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 34 publications
0
28
0
2
Order By: Relevance
“…One of the most common findings in the studies considered for this review, is that patients with mental illnesses typically had lower vaccination rates or more vaccination hesitancy ( Eyllon et al, 2022 ; Huang et al, 2021 ; Jefsen et al, 2021 ; Bai et al, 2021 ; Perlis et al, 2022 ; Hao et al, 2021 ) confirming a numerous studies suggesting this (Wang et al, 2021). Specifically, individuals with severe mental illness, including schizophrenia, were least likely to accept vaccination ( Huang et al, 2021 ; Bai et al, 2021 ; Tzur Bitan et al, 2021 ; Raffard et al, 2022). This was often attributed to barriers including mental health and disorder stigma and impaired decision-making skills ( Huang et al, 2021 ; Tzur Bitan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…One of the most common findings in the studies considered for this review, is that patients with mental illnesses typically had lower vaccination rates or more vaccination hesitancy ( Eyllon et al, 2022 ; Huang et al, 2021 ; Jefsen et al, 2021 ; Bai et al, 2021 ; Perlis et al, 2022 ; Hao et al, 2021 ) confirming a numerous studies suggesting this (Wang et al, 2021). Specifically, individuals with severe mental illness, including schizophrenia, were least likely to accept vaccination ( Huang et al, 2021 ; Bai et al, 2021 ; Tzur Bitan et al, 2021 ; Raffard et al, 2022). This was often attributed to barriers including mental health and disorder stigma and impaired decision-making skills ( Huang et al, 2021 ; Tzur Bitan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 60%
“… Eyllon et al (2022) Cross-sectional study Northeastern United States n = 14 365 patients of a group medical practice Outcome measures: online survey Main Findings: Substance and tobacco use disorders had vaccine hesitancy after regression analysis of sociodemographic factors; Medicaid payer type, lower education, income and Hispanic, female, and African American groups were associated with more vaccine hesitancy; younger respondents and those with lower socioeconomic status were more likely to report vaccination resistance. More vaccine hesitancy across all psychiatric comorbidities except Alcohol Use Disorders Huang et al (2021) Cross-sectional study Wuhan, China N = 906 adult patients with mental disorders Outcome measures: self-administered questionnaire Main findings: Higher education, a good family financial status, believing that over 50% of vaccine recipients would be immune to COVID-19, not being worried about side-effects, being out-patients, having mental disorders other than psychosis significantly associated with vaccine uptake 2.psychotic disorders were least likely to take the vaccine Jefsen et al, 2021 Cross-sectional study Danish Population n = 992 patients from psychiatric services Outcome measures: questionnaire-based online surveys Main findings: Younger age and mental illness were associated with lower vaccination willingness; Reasons for vaccine hesitancy: safety concerns, vaccines not sufficiently tested, vaccination unnecessary, lack of trust in authorities Uvais (2021) Cross-sectional study Indian population N = 90 patients of an outpatient psychiatry department Outcome measures: Covid-19 related questionnaire Main findings: Patients with higher education had more intentions of vaccination; Islamic participants had significantly higher vaccine hesitancy; Significantly higher vaccine hesitancy in this population in comparison to other global populations. Bai et al, 2021 Cross-sectional study Chinese Population N = 1853 outpatients and inpatients associated with 6 psychiatric hospitals Outcome measures: survey containing items from the WHO Quality of Life Scale Brief version (WHOQOL-BREF), the Visual Analog Scale for Pain (VAS), Patient Health Questionnaire-2 (PHQ-2), Social Impact Scale (SIS) Main findings: ...…”
Section: Resultsmentioning
confidence: 99%
“…However, a study in Denmark found that vaccine willingness for preventing COVID-19 was lower amongst individuals with mental disorders, compared with the general population [ 21 ]. A study in China found that individuals with mental disorders had a much lower rate of vaccination than the general population [ 22 ]. These studies have suggested that it is necessary to develop strategies for increasing vaccination coverage among individuals with mental disorders [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in China found that individuals with mental disorders had a much lower rate of vaccination than the general population [ 22 ]. These studies have suggested that it is necessary to develop strategies for increasing vaccination coverage among individuals with mental disorders [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the initial COVID-19 vaccination campaign in 2021, in some countries like Denmark, the Netherlands, the UK, and Germany populations with severe mental illness were prioritized for vaccination [9] but it remained unclear to what degree at-risk groups with mental illness were reached by vaccination campaigns in every-day routine health-care practice. Studies on vaccination rates of populations with mental illness in comparison to the general population showed heterogenous results: In some studies vaccination rates were comparable to or better than the general population [10][11][12][13] but in others people with mental illness showed much lower vaccination rates [14][15][16][17]. A common factor for vaccination rates similar to the general population seemed to be vaccination offerings by mental health institutions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%